Densitas Gizi dan Morbiditas serta Hubungannya dengan Status Gizi Anak Usia Prasekolah Pedesaan - Davidson, Sarah Melati; Dwiriani, Cesilia Meti; Khomsan, Ali (Media Kesehatan Masyarakat Indonesia, 2018)
School age children are susceptible to experiencing nutritional problems, one of which is due to environmental factors, especially the physical environment which provides broad, affordable food, higher energy density and lack of consumption of fruits and vegetables. The efforts to improve the habit of eating fruits and vegetables in school children is the existence of school based intervention. This study aim to analyze the effect of school based intervention program to increase of fruit and vegetable consumption of elementary school students. The study took place from February to May 2017 in Nganjuk, East Java. This study used experimental design with pre-post intervention with the number of subjects is 50 students (10-13 years) given three types of interventions is school gardening, cooking class, and giving of fruit and vegetables in school. The results showed that the presence of these three interventions can increased fruit consumption 130 g/day and vegetable 100 g/day and the availability of fruit and vegetables at home increased 81 g/week and 182 g/week. The results from recall SQ-FFQ 2x24 hours showed the average consumption of energy density decreased from 1420 kcal to 1241 kcal. Based on these results, school based intervention can be used as a strategy to increase fruit and vegetable consumption and availability fruit and vegetable at home